Fully factorise :
Problem 1 :
ab + ac – 2a
Solution :
Given, ab + ac – 2a
We find a in common in all three terms, we factor "a" out
a(b + c - 2)
Problem 2 :
a2b2 – 2ab
Solution :
Given, a2b2 – 2ab
Factoring ab, we get
ab(ab - 2)
Problem 3 :
18x – 2x3
Solution :
= 18x – 2x3
= 2x(9 – x2)
= 2x(32 - x2)
= 2x(3 + x) (3 - x)
Problem 4 :
x2 + 14x + 49
Solution :
= x2 + 14x + 49
By decomposing the middle term, we get
= x2 + 7x + 7x + 49
= x(x + 7) + 7(x + 7)
= (x + 7)(x + 7)
= (x + 7)2
Problem 5 :
4a3 – 4ab2
Solution :
= 4a3 – 4ab2
= 4a(a2 – b2)
Using the algebraic identity, a2 – b2 = (a + b)(a - b)
= 4a(a + b) (a - b)
Problem 6 :
x3y – 4xy
Solution :
= x3y – 4xy
= xy(x2 - 4)
= xy(x2 - 22)
= xy(x + 2) (x - 2)
Problem 7 :
4x4 – 4x2
Solution :
= 4x4 – 4x2
= 4x2(x2 - 1)
= 4x(x + 1) (x - 1)
Problem 8 :
(x - 2)y – (x - 2)z
Solution :
= (x - 2)y – (x - 2)z
= (x - 2)(y - z)
Problem 9 :
(x + 1)a + (x + 1)b
Solution :
= (x + 1)a + (x + 1)b
= (x + 1)[a + b]
Problem 10 :
(x - y)a + (x - y)
Solution :
= (x - y)a + (x - y)
(x - y)(a + 1)
Problem 11 :
x(x + 2) + 3(x + 2)
Solution :
= x(x + 2) + 3(x + 2)
= (x + 2)(x + 3)
Problem 12 :
x3 + x2 + x + 1
Solution :
= x3 + x2 + x + 1
= x2(x + 1) + 1(x + 1)
= (x2 + 1) (x + 1)
Factorise completely :
Problem 13 :
7x - 35y
Solution :
= 7x - 35y
Factoring 7, we get
= 7(x - 5y)
Problem 14 :
= 2g2 - 8
Solution :
= 2g2 - 8
Factoring 2, we get
= 2(g2 - 4)
Problem 15 :
-5x2 - 10x
Solution :
= -5x2 - 10x
Factoring -5x, we get
= -5x(x + 2)
Problem 16 :
m2 + 3mp
Solution :
= m2 + 3mp
= m(m + 3p)
Problem 17 :
a2 + 8a + 15
Solution :
= a2 + 8a + 15
= a2 + 3a + 5a + 15
= a(a + 3) + 5(a + 3)
= (a + 3) (a + 5)
Problem 18 :
m2 - 6m + 9
Solution :
= m2 - 6m + 9
= m2 - 3m - 3m + 9
= m(m - 3) - 3(m - 3)
= (m - 3)2
Problem 19 :
5x2 + 5xy - 5x2y
Solution :
= 5x2 + 5xy - 5x2y
= 5x(x + y - xy)
Problem 20 :
xy + 2x + 2y + 4
Solution :
= xy + 2x + 2y + 4
= x(y + 2) + 2(y + 2)
= (x + 2) (y + 2)
Problem 21 :
y2 + 5y - 9y - 45
Solution :
= y2 + 5y - 9y - 45
= y(y + 5) - 9(y + 5)
= (y - 9) (y + 5)
Problem 22 :
2x2 + 10x + x + 5
Solution :
= 2x2 + 10x + x + 5
= 2x(x + 5) + (x + 5)
= (2x + 1) (x + 5)
Problem 23 :
3y2 - 147
Solution :
= 3y2 - 147
= 3 (y2 - 49)
= 3(y2 - 72)
= 3(y + 7) (y - 7)
Problem 24 :
3p2 - 3q2
Solution :
= 3p2 - 3q2
= 3(p2 - q2)
= 3(p + q) (p - q)
Problem 25 :
4c2 - 1
Solution :
= 4c2 - 1
= (2c)2 - 12
= (2c - 1) (2c + 1)
Problem 26 :
3x2 + 3x - 36
Solution :
= 3x2 + 3x - 36
= 3(x2 + x - 12)
= 3(x2 - 3x + 4x - 12)
= 3(x(x - 3) + 4(x - 3))
= 3(x - 3) (x - 4)
Problem 27 :
2bx - 6b + 10x - 30
Solution :
= 2bx - 6b + 10x - 30
= 2(bx - 3b + 5x - 15)
= 2(b(x - 3) + 5(x - 3))
= 2(x - 3) (b + 5)
Fully factorise :
Problem 28 :
12 - 11x - x2
Solution :
= 12 - 11x - x2
= -x2 - 11x + 12
= -(x2 + 11x - 12)
= -(x2 - x + 12x - 12)
= -(x(x - 1) + 12(x - 1))
= -(x + 12) (x - 1)
Problem 29 :
-2x2 - 6 + 8x
Solution :
= -2x2 - 6 + 8x
= -2x2 + 8x - 6
= -2(x2 - 4x + 3)
= -2(x2 - x - 3x + 3)
= -2(x(x - 1) - 3(x - 1))
= -2(x - 1) (x - 3)
Problem 30 :
14 - x2 - 5x
Solution :
= 14 - x2 - 5x
= -x2 - 5x + 14
= -(x2 + 5x - 14)
= -(x2 - 2x + 7x - 14)
= -(x(x - 2) + 7(x - 2))
= -(x + 7) (x - 2)
Problem 31 :
4x2 - 2x3 - 2x
Solution :
= 4x2 - 2x3 - 2x
= 2x(2x - x2 - 1)
2x(-x2 + 2x - 1)
2x(-(x2 - 2x + 1))
2x(-(x - 1)2)
-2x(x - 1)2
Problem 32 :
(a + b)2 - 9
Solution :
= (a + b)2 - 9
= (a + b)2 - 32
= (a + b - 3) (a + b + 3)
Problem 33 :
(x + 2)2 - 4
Solution :
= (x + 2)2 - 4
Let t = (x + 2)
= t2 - 22
= (t + 2)(t - 2)
Applying the value of t, we get
= (x + 2 + 2) (x + 2 - 2)
= (x + 4)(x)
= x (x + 4)
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM